Mapping Artisanal and Small‐Scale Gold Mining in Senegal Using Sentinel 2 Data. (30th November 2020) - Ngom, N. M.; Mbaye, M.; Baratoux, D.; Baratoux, L.; Catry, T.; Dessay, N.; Faye, G.; Sow, E. H.; Delaitre, E.
Abstract: Artisanal and small‐scale gold mining (ASGM) represents a significant economic activity for communities in developing countries. In southeastern Senegal, this activity has increased in recent years and has become the main source of income for the local population. However, it is also associated with negative environmental, social, and health impacts. Considering the recent development of ASGM in Senegal and the difficulties of the government in monitoring and regulating this activity, this article proposes a method for detecting and mapping ASGM sites in Senegal using Sentinel 2 data and the Google Earth Engine. Two artisanal mining sites in Senegal are selected to test this approach. Detection and mapping are achieved following a processing pipeline. Principal component analysis (PCA) is applied to determine the optimal period of the year for mapping. Separability and threshold (SEaTH) is used to determine the optimal bands or spectral indices to discriminate ASGM from other land use. Finally, automatic classification and mapping of the scenes are achieved with support vector machine (SVM) classifier. The results are then validated based on field observations. The PCA and examination of spectral signatures as a function of time indicate that the best period for discriminate ASGM sites against other types of land use is the end of dry season, when vegetation is minimal. The classification results are presented as a map with different categories of land use. This method could be applied to future Sentinel scenes to monitor the evolution of mining sites and may also be extrapolated to other relevant areas in the Sahel. Plain Language Summary: In recent years, artisanal and small‐scale gold mining (ASGM) has become a significant source of income for communities in southeastern Senegal. However, this activity is also associated with negative environmental and social impacts. The lack of information regarding the constantly evolving geographical distribution and extent of the mining sites is an obstacle for the regulations of this activity by the government. To fill this gap, we have elaborated and tested a method using publicly available multispectral remote sensing data (Sentinel 2) and a cloud computing service (Google Earth Engine). The objective maps of environmental impacts produced by this method shall lead to a better knowledge of the areas affected by artisanal mining activities in the Sahelian region. This low‐cost approach, using public data and computing resources, is designed to become a decision support tool for governments of developing countries. Key Points: artisanal and small‐scale gold mining Sentinel 2 Google Earth Engine